Effect of group virtual exercise on people with Parkinson's disease: A randomized controlled trial. - Fishel, Sarah C.; Hotchkiss, Megan E.; McNamara, Christine A.; Sevilla, Kaitlyn M.; Brown, Samantha A. (Physiotherapy Theory & Practice, 2025)
Background: For people with Parkinson's disease (PwPD), high-intensity exercise in individual or group format can improve function and quality of life (QoL). Individualized virtual exercise programs have been effective for people with PD, but the feasibility and impact of group exercise in the virtual format has not been investigated. Purpose: To compare the effect of individual and group virtual exercise on functional mobility and QoL for PwPD. Methods: Twenty PwPD were randomized to individualized (n = 10) or group (n = 10) virtual exercise 2 times per week for 8 weeks. Exercises were multi-dimensional, and intensity was monitored with a wrist-worn heart rate (HR) monitor. Outcomes were assessed before and after the program, including standing balance, gait speed, gait endurance, motor function, QoL, and self-efficacy. Within-and between-group changes were analyzed using a mixed model analysis of variance (ANOVA) and nonparametric tests were used for analysis. Results: Participants attended over 75% of scheduled sessions. Within-group analysis showed statistically significant improvements in Five Times Sit-to-Stand (p <.01), mini-BESTest (p =.03), comfortable (p <.01) and fast gait speeds (p =.02), and gait endurance (p <.01) with large effect sizes (partial eta squared > 0.25). There were no statistically significant differences between groups on any outcomes (p >.09). In more than 70% of sessions, participants reached an exercise intensity ≥ 65% HR maximum. Conclusion: This high-intensity, virtual exercise program was safe and effective at improving balance and functional mobility for community-dwelling PwPD in individual and group format. Virtual exercise programs, either in an individual or group format, can increase access to high-quality programs for PwPD.